THE ARTISTIC SIGNIFICANCE OF THE JAHON OTIN UVAYSI LYRIC - Abdurahmonova Mavluda Ibragimovna (Western European Studies, 2024)
The Uzbek poet and lyricist, Uvaysi, is a prominent figure in the realm of Central Asian literature. Born in the 17th century, Uvaysi's works have had a profound impact on the cultural heritage of Uzbekistan, leaving an indelible mark on the nation's literary landscape. This article will delve into the life and works of Uvaysi, exploring his poetic style, thematic concerns, and the significance of his contributions to Uzbek literature
Keywords: early life; background; lyrics